Heat-resistant friction reinforcement sheet for tennis shoe upper and method for manufacturing the same

CN122978554APending Publication Date: 2026-10-27YOUTH HOME FUJIAN SPORTS GOODS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611099081.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

橡胶自身的耐磨潜力和耐热性优于热塑性聚氨酯,但常规硫化后自然冷却的工艺存在缺陷:橡胶交联网络在模压硫化阶段处于高能态,缓慢冷却过程中分子链有足够时间发生局部重排和应力松弛,最终保留在室温下的网络结构已非硫化完成瞬间的状态

Benefits of technology

1、补强片在升温工况下的耐磨损性能得到提高。经测试,在30℃条件下,本发明补强片的DIN磨损量可低至34.2mm3;在100℃条件下经30min热处理后,DIN磨损量仍可控制在37.8mm3,远低于标准限值≤50mm3。在30℃至100℃温度区间内,本发明补强片的DIN磨损值稳定在34.2~49mm3之间,始终满足≤50mm3的技术要求,表明其在宽温域范围内具有优异且稳定的热耐磨性能,摩擦损耗极低。2、补强片在高温工况下的耐磨性能较同类产品优势明显。在60℃条件下,本发明补强片的DIN磨损量较同配方自然冷却的硫化橡胶样片减少约44%,较市售KPU补强片减少约63%。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978554A_ABST
    Figure CN122978554A_ABST
Patent Text Reader

Abstract

The application discloses a kind of tennis shoe upper heat-resistant friction reinforcing sheet and its preparation method, belong to shoe rubber product technical field.The reinforcing sheet is made of mixing rubber by moulding vulcanization and freeze setting, and mixing rubber includes by weight parts: cis-butadiene rubber: 60-70, polyisoprene rubber: 10-20, ethylene-propylene-diene rubber: 20-30, silicon dioxide: 30-50, wear-resistant oil: 5-10, four acicular zinc oxide whisker: 3-8, 2-thiol group methyl benzimidazole antioxidant: 1-3, stearic acid: 0.5-1.5, PEG-4000: 1-3, protective wax: 0.5-1.5.The thickness of reinforcing sheet is 1.0-2.5mm.Preparation time is pressed into thin rubber sheet after mixing each component, moulding vulcanization, 30s after opening mould is transferred into-10 DEG C to-5 DEG C freeze environment and is handled for 15-30min.The obtained reinforcing sheet is fixed by cold adhesive and high-frequency current or hot-pressing and tennis shoe upper inner side.The wear resistance of the reinforcing sheet is superior to natural cooling of the same formula vulcanized rubber sheet and commercially available KPU reinforcing sheet under temperature rising condition, and the edge is not easy to crack after being heated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of rubber products for footwear, specifically relating to a heat-resistant friction reinforcing sheet for tennis shoe uppers and its manufacturing method. Background Technology

[0002] Tennis involves numerous lateral stops and sliding movements, causing frequent and intense friction between the inside of the athlete's foot and hard surfaces. To delay wear and tear on the shoe upper, manufacturers typically attach a durable reinforcing patch to the stress zone on the inside of the tennis shoe upper. This small patch, however, is a crucial component determining the lifespan of a professional tennis shoe during gameplay.

[0003] Currently, most commercially available tennis shoes use thermoplastic polyurethane (KPU) for this area. While KPU's abrasion resistance at room temperature is sufficient for general athletic intensity, its hydrogen bonds between molecular chains are sensitive to temperature changes. During high-intensity competition, the continuous heat generated by the foot raises the temperature inside the shoe cavity to 40-60°C. As this heat is conducted from the inside out to the surface of the shoe, the KPU softens, and the rate of mass loss under friction conditions increases exponentially. In actual use, a pair of high-end tennis shoes can develop a hole on the inner side of the upper within hours during high-intensity matches played by professional players.

[0004] Some manufacturers are attempting to replace KPU with vulcanized rubber sheets. While rubber itself offers superior abrasion resistance and heat resistance compared to thermoplastic polyurethane, the conventional natural cooling process after vulcanization has drawbacks: the rubber crosslinking network is in a high-energy state during the molding vulcanization stage. During slow cooling, the molecular chains have sufficient time for local rearrangement and stress relaxation, resulting in a network structure at room temperature that is not in the state immediately following vulcanization. When this naturally cooled rubber sheet is reheated, the relaxed crosslinked sections soften first, leading to a significant difference in high-temperature abrasion resistance compared to the theoretical level immediately after vulcanization. Simply replacing the material with rubber without changing the cooling method has limited effectiveness in addressing the high-temperature wear problem of tennis shoe uppers.

[0005] Another engineering constraint comes from the requirement for lightweight uppers. The thickness of the reinforcing sheet must be controlled within 2.5mm, otherwise the stiffness of the shoe body will affect foot flexibility. The mixing uniformity, sheeting accuracy, and vulcanization control of thin rubber sheets are all challenging, placing more stringent demands on formulation design and process parameters.

[0006] In summary, it is necessary to provide a reinforcing sheet that can maintain a high wear resistance level under heated friction conditions and has a thickness suitable for use in shoe uppers, as well as a method for its preparation. Summary of the Invention

[0007] The purpose of this invention is to provide a heat-resistant friction reinforcing sheet for tennis shoe uppers and its manufacturing method.

[0008] To achieve the above objectives, the present invention provides the following technical solution: A heat-resistant friction reinforcement sheet for tennis shoe uppers is made from a compound rubber comprising the following components by weight, which is then molded, vulcanized, and freeze-set: the freeze-setting process involves transferring the sheet, which is still at a temperature of 140-160°C after molding and vulcanization, into a freezing environment of -10°C to -5°C within 30 seconds and treating it for 15-30 minutes. The compound comprises: Butadiene rubber: 60-70 parts; Polyisoprene rubber: 10-20 parts; EPDM rubber: 20-30 parts; Silica: 30-50 parts; Wear-resistant oil: 5-10 parts; Tetraneous zinc oxide whiskers: 3-8 parts; Sulfur: 1.5-2.5 parts; Vulcanization accelerator: 1-3 parts; 2-Methylbenzimidazole antioxidant: 1-3 parts; Stearic acid: 0.5-1.5 parts; PEG-4000: 1-3 parts; Protective wax: 0.5-1.5 parts.

[0009] Furthermore, the thickness of the reinforcing sheet is 1.0-2.5 mm.

[0010] Furthermore, the vulcanization accelerator is at least one of N-cyclohexyl-2-benzothiazole sulfenamide, dibenzothiazole disulfide, and tetramethylthiuram disulfide; the amount of sulfur used is 1.8-2.2 parts, and the amount of the vulcanization accelerator used is 1.5-2.5 parts.

[0011] Furthermore, the silica is precipitated silica.

[0012] Furthermore, the amount of the four needle-shaped zinc oxide whiskers is 4-6 parts.

[0013] Furthermore, the wear-resistant oil is an aromatic oil or a naphthenic oil.

[0014] A method for preparing a heat-resistant friction-reinforcing sheet for tennis shoe uppers includes the following steps: (1) Put the ingredients of the formula into an internal mixer and mix them evenly to make a compound; (2) Press the compounded rubber into a thin sheet with a thickness of 1.0-2.5 mm; (3) Place the thin film in a mold and mold it at a temperature of 140-160℃ and a pressure of 10-15MPa for 5-10 minutes to obtain a high-temperature sheet; (4) Transfer the high-temperature sheet to a freezing environment of -10°C to -5°C within 30 seconds and freeze-set for 15-30 minutes to obtain the reinforcing sheet.

[0015] Furthermore, it also includes step (5): grinding or corona treating the bonding surface of the reinforcing sheet, applying cold adhesive, and then bonding and fixing it to the inner side of the tennis shoe upper by high-frequency current or hot pressing.

[0016] Further, in step (1), butadiene rubber, polyisoprene rubber and ethylene propylene diene monomer rubber are first plasticized, and then 2-thiol-methylbenzimidazole antioxidant, stearic acid, PEG-4000 and protective wax are added. After mixing, silica, tetraneedle zinc oxide whiskers and wear-resistant oil are added, and then sulfur and vulcanization accelerator are added and mixed until uniform.

[0017] Furthermore, the compound obtained in step (1) has a Mooney viscosity ML(1+4)@100℃ of 50-70.

[0018] The beneficial effects of this invention are as follows: 1. The wear resistance of the reinforcing sheet is improved under heated conditions. Tests show that at 30℃, the DIN wear of the reinforcing sheet of this invention can be as low as 34.2mm. 3 After heat treatment at 100℃ for 30 minutes, the DIN wear can still be controlled at 37.8mm. 3 It is far below the standard limit of ≤50mm 3 Within a temperature range of 30°C to 100°C, the DIN wear value of the reinforcing sheet of this invention remains stable at 34.2–49 mm. 3 The thickness must always be ≤50mm. 3 The technical requirements indicate that it possesses excellent and stable thermal wear resistance over a wide temperature range, with extremely low friction loss. 2. The wear resistance of the reinforcing sheet under high-temperature conditions is significantly superior to similar products. At 60℃, the DIN wear of the reinforcing sheet of this invention is reduced by approximately 44% compared to naturally cooled vulcanized rubber samples with the same formulation, and by approximately 63% compared to commercially available KPU reinforcing sheets.

[0019] 3. When EPDM rubber is used in combination with butadiene rubber and polyisoprene rubber, and with the freeze-setting process, the reinforcing sheet maintains high tear strength after being heated, and the edges are not prone to cracking due to repeated friction.

[0020] 4. The reinforcing sheet has high adhesive peel strength and excellent bonding firmness. Tests show that, under a sampling width of 10mm±2, the peel strength at the interface between the reinforcing sheet and the shoe upper reaches 4.53kgf / cm, far exceeding the standard requirement of ≥3.0kgf / cm. It can withstand the high-frequency lateral shear forces encountered in tennis and will not warp or detach even after long-term use.

[0021] 5. When EPDM rubber is used in combination with butadiene rubber and polyisoprene rubber, and with the freeze-setting process, the reinforcing sheet maintains high tear strength after being heated, and the edges are not prone to cracking due to repeated friction.

[0022] 6. The reinforcing plate is fused to the inside of the shoe upper with cold adhesive and high-frequency current or hot pressing. The bonding strength can withstand the high-frequency lateral shear force during tennis, and it will not curl up or fall off after long-term use. Attached Figure Description

[0023] Figure 1 This is a flowchart illustrating the preparation method of a heat-resistant friction-reinforcing sheet for tennis shoe uppers. Detailed Implementation

[0024] The present invention will be further illustrated below with reference to embodiments and comparative examples. These embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the present invention.

[0025] Raw material description The raw materials used in the examples and comparative examples are as follows: Butadiene rubber, with a cis-1,4 structure content ≥96%, has a Mooney viscosity ML(1+4)@100℃ of 45-55; Polyisoprene rubber, with a cis-1,4 structure content ≥96%; Ethylene propylene diene monomer (EPDM) rubber, with an ethylene content of approximately 53%, ENB type third monomer, and a Mooney viscosity ML(1+4)@100℃ of 50-60; Silica, precipitated silica, BET specific surface area 175m² 2 / g; Wear-resistant oil, aromatic oil; Four needle-like zinc oxide whiskers, with needle lengths of 10-30 μm and root diameters of 0.5-2 μm; 2-Methylbenzimidazole antioxidant, also known as antioxidant MMBZ; PEG-4000, number average molecular weight 4000; Stearic acid, iodine value ≤0.5; Protective wax, microcrystalline wax, melting point 65-70℃. Example 1

[0026] Take 65 parts of butadiene rubber, 15 parts of polyisoprene rubber, 20 parts of EPDM rubber, 40 parts of silica, 8 parts of aromatic oil, 5 parts of tetraneedle-shaped zinc oxide whiskers, 2.0 parts of sulfur, 1.5 parts of N-cyclohexyl-2-benzothiazole sulfenamide, 0.5 parts of tetramethylthiuram disulfide, 2 parts of 2-mercaptomethylbenzimidazole antioxidant, 1.0 part of stearic acid, 2 parts of PEG-4000, and 1.0 part of protective wax.

[0027] The preparation steps are as follows.

[0028] Step (1), mixing. Butadiene rubber, polyisoprene rubber, and ethylene propylene diene monomer (EPDM) rubber were added to a mixer and plasticized for 3 minutes, with the temperature rising to approximately 90°C. 2-Methylbenzimidazole antioxidant, stearic acid, PEG-4000, and protective wax were added, and mixing continued for 2 minutes. Silica, tetraneedle-shaped zinc oxide whiskers, and aromatic oil were then added, and mixing continued for 6 minutes until no powder agglomeration was visually observed. Then, 2.0 parts of sulfur, 1.5 parts of N-cyclohexyl-2-benzothiazole sulfenamide, and 0.5 parts of tetramethylthiuram disulfide were added, and mixing continued for approximately 2 minutes until homogeneous. The discharge temperature was 116°C, yielding the compound. A sample was tested using a Mooney viscometer, preheated at 100°C for 1 minute and rotated for 4 minutes. The ML(1+4)@100°C value was 58.

[0029] Step (2), sheeting. The compounded rubber is turned on a two-roll mill for 2 minutes, and then pressed into a thin sheet with a thickness of 1.5 mm through a three-roll calender. The roller temperature is controlled at 50-60℃. The thin sheet is cut to the size that matches the mold cavity.

[0030] Step (3), compression molding and vulcanization. Place the thin film in the mold of the flat vulcanizing machine with the mold temperature stabilized. The mold cavity size corresponds to the shape of the inner reinforcing area of ​​the tennis shoe upper. The upper mold temperature is 150℃, the lower mold temperature is 150℃, the clamping pressure is 13MPa, and the vulcanization time is 8min. Open the mold after vulcanization.

[0031] Step (4), freezing and shaping. Within 25 seconds after mold opening, the high-temperature sheet is removed from the mold, laid flat and transferred to an industrial freezer at -8℃. Cold air is circulated in the freezer, and gaps are left between the sheets. After freezing for 20 minutes, the sheet is removed and the surface temperature drops to -6℃, thus obtaining the reinforcing sheet, with a thickness of 1.5mm.

[0032] Step (5), bonding. Grind the side of the reinforcing sheet intended for bonding with a grinding wheel to remove the smooth surface film, exposing a slightly roughened surface. Apply cold adhesive evenly to the ground surface, with a layer thickness of approximately 0.1 mm, and allow it to dry until semi-dry. Place the reinforcing sheet on the predetermined drag area inside the tennis shoe upper and press it together using a high-frequency plastic welding machine at a frequency of 27.12 MHz for 6 seconds to complete the bonding. A flowchart of a method for preparing a heat-resistant friction reinforcing sheet for tennis shoe uppers is shown below. Figure 1 . Example 2

[0033] Take 70 parts of butadiene rubber, 10 parts of polyisoprene rubber, 20 parts of EPDM rubber, 45 parts of silica, 10 parts of aromatic oil, 6 parts of tetraneedle-shaped zinc oxide whiskers, 2.2 parts of sulfur, 2.0 parts of N-cyclohexyl-2-benzothiazole sulfenamide, 2.5 parts of 2-mercaptomethylbenzimidazole antioxidant, 1.2 parts of stearic acid, 2.5 parts of PEG-4000, and 1.2 parts of protective wax.

[0034] The preparation steps differ from those in Example 1 as follows: In step (1), the discharge temperature is 118℃, and the Mooney viscosity ML(1+4)@100℃ of the prepared compound is 65. In step (2), the thickness of the thin film is pressed to 2.0 mm. In step (3), the vulcanization temperature is 155℃, the pressure is 14 MPa, and the vulcanization time is 7 min. In step (4), the high-temperature sheet is transferred to a -5℃ freezing environment within 20 s after mold opening and treated for 15 min. In step (5), the bonding surface is treated with a corona discharge machine instead of polishing, and the rest is the same as in Example 1. The thickness of the resulting reinforcing sheet is 2.0 mm. Example 3

[0035] Take 60 parts of butadiene rubber, 15 parts of polyisoprene rubber, 25 parts of EPDM rubber, 35 parts of silica, 6 parts of aromatic oil, 4 parts of tetraneedle-shaped zinc oxide whiskers, 1.8 parts of sulfur, 1.2 parts of dibenzothiazole disulfide, 1.5 parts of 2-mercaptomethylbenzimidazole antioxidant, 0.8 parts of stearic acid, 1.5 parts of PEG-4000, and 0.8 parts of protective wax.

[0036] The preparation steps differ from those in Example 1 as follows: In step (1), the discharge temperature is 112℃, and the Mooney viscosity ML(1+4)@100℃ of the prepared compound is 53. In step (2), the thickness of the thin film is pressed to 1.2mm. In step (3), the vulcanization temperature is 145℃, the pressure is 12MPa, and the vulcanization time is 9min. In step (4), the high-temperature sheet is transferred to a -10℃ freezing environment within 30s after mold opening and treated for 25min. Step (5) is the same as in Example 1. The thickness of the resulting reinforcing sheet is 1.2mm. Example 4

[0037] Take 68 parts of butadiene rubber, 12 parts of polyisoprene rubber, 20 parts of EPDM rubber, 50 parts of silica, 7 parts of aromatic oil, 5 parts of tetraneedle-shaped zinc oxide whiskers, 2.5 parts of sulfur, 1.8 parts of N-cyclohexyl-2-benzothiazole sulfenamide, 0.7 parts of tetramethylthiuram disulfide, 2 parts of 2-mercaptomethylbenzimidazole antioxidant, 1.5 parts of stearic acid, 3 parts of PEG-4000, and 1.5 parts of protective wax.

[0038] The preparation steps differ from those in Example 1 as follows: In step (1), the discharge temperature is 120℃, and the Mooney viscosity ML(1+4)@100℃ of the prepared compound is 68. In step (2), the thickness of the thin film is pressed to 2.5mm. In step (3), the vulcanization temperature is 160℃, the pressure is 15MPa, and the vulcanization time is 5min. In step (4), the high-temperature sheet is transferred to a -5℃ freezing environment within 18s after mold opening and treated for 15min. Step (5) is the same as in Example 1. The thickness of the resulting reinforcing sheet is 2.5mm. Example 5

[0039] Take 62 parts of butadiene rubber, 18 parts of polyisoprene rubber, 20 parts of EPDM rubber, 30 parts of silica, 5 parts of aromatic oil, 3 parts of tetraneedle-shaped zinc oxide whiskers, 1.5 parts of sulfur, 1.0 part of dibenzothiazole disulfide, 1 part of 2-mercaptomethylbenzimidazole antioxidant, 0.5 parts of stearic acid, 1 part of PEG-4000, and 0.5 parts of protective wax.

[0040] The preparation steps differ from those in Example 1 as follows: In step (1), the discharge temperature is 108℃, and the Mooney viscosity ML(1+4)@100℃ of the prepared compound is 50. In step (2), the thickness of the thin film is pressed to 1.0 mm. In step (3), the vulcanization temperature is 140℃, the pressure is 10 MPa, and the vulcanization time is 10 min. In step (4), the high-temperature sheet is transferred to a -10℃ freezing environment within 30 s after mold opening and treated for 30 min. Step (5) is the same as in Example 1. The thickness of the resulting reinforcing sheet is 1.0 mm.

[0041] Comparative Example 1 A compound rubber prepared using the same formulation and mixing steps as in Example 1, comprising 2.0 parts sulfur, 1.5 parts N-cyclohexyl-2-benzothiazole sulfenamide, 0.5 parts tetramethylthiuram disulfide, and all other components, was pressed into a 1.5 mm thick sheet and molded and vulcanized at 150°C and 13 MPa for 8 minutes. After demolding, the sheet was removed and allowed to cool naturally to room temperature to obtain the reinforcing sheet.

[0042] Comparative Example 2 Commercially available KPU tennis shoe upper reinforcement plates, 1.5mm thick.

[0043] Comparative Example 3 A compound with the same formulation as in Example 1, comprising 2.0 parts sulfur, 1.5 parts N-cyclohexyl-2-benzothiazole sulfenamide, 0.5 parts tetramethylthiuram disulfide, and all other components, was pressed into a 1.5 mm thick sheet and vulcanized at 150°C and 13 MPa for 8 minutes. After demolding, the sheet was removed and allowed to stand naturally for 10 minutes to allow the sheet temperature to drop to approximately 80°C. It was then transferred to a -8°C freezer for 20 minutes to obtain the reinforcing sheet.

[0044] Samples were cut from the reinforcing sheets of Examples 1-5 and Comparative Examples 1-3, and the DIN wear amount was tested according to the GB / T9867 method. Test conditions: The samples were placed in a 60℃ oven for 30 minutes, and immediately after removal, the wear test was performed at an ambient temperature of 60℃. Each sample was tested 3 times and the average value was taken.

[0045] The wear test results are shown in Table 1 below: Table 1: Test Results of DIN Wear Amount in Multiple Temperature Ranges for Examples and Comparative Examples (Unit: mm) 3 ) Example 1 34.2 35.0 36.5 37.2 37.5 37.8 Example 2 35.1 35.8 37.0 37.9 38.3 38.6 Example 3 36.0 36.7 38.2 39.1 39.5 40.0 Example 4 35.6 36.3 37.8 38.5 39.0 39.4 Example 5 36.8 37.5 39.0 40.2 40.8 41.5 Comparative Example 1 62 83 112 138 156 172 Comparative Example 2 85 120 178 210 235 258 Comparative Example 3 55 68 85 102 115 127 As can be seen from Table 1: (1) Examples 1-5 showed excellent thermal wear resistance stability in the entire test temperature range from 30℃ to 100℃, and the DIN wear value of each example was less than 50mm at all temperature points. 3 The standard limit is 34.2 mm for DIN wear in Example 1 at 30°C. 3 After heat treatment at 100℃ for 30 minutes, the DIN wear amount is only 37.8mm. 3 It is far superior to the standard requirements.

[0046] (2) Comparative Example 1 has the same formulation as Example 1 but uses natural cooling. At 30°C, the DIN wear is 62 mm. 3 This exceeds the standard limit; the wear increases dramatically with rising temperature, reaching as high as 172 mm at 100℃. 3 This indicates that the natural cooling process cannot obtain a stable heat-resistant cross-linked network.

[0047] (3) The DIN wear of the KPU material in Comparative Example 2 is 85mm at room temperature (30℃). 3 It can no longer meet the requirement of ≤50mm 3 The wear rate increases significantly after heating, reaching as high as 258 mm at 100℃. 3 This indicates that KPU material is not suitable for high-temperature friction conditions.

[0048] (4) Although Comparative Example 3 was subjected to freezing treatment, the cross-linking network was partially loosened due to delayed freezing. Its wear was significantly higher than that of Examples 1-5 at all temperature points, proving that freezing immediately after vulcanization is crucial to obtaining excellent thermal wear resistance.

[0049] Peel strength test The reinforcing sheets from Examples 1-5 were respectively attached to the inner side of the upper of the same tennis shoe. The peel strength of the bonding interface was tested according to the method of GB / T3903.12, with a sampling width of 10mm ± 2. The test results are shown in Table 2: Table 2: Peel Strength Test Results of Examples and Comparative Examples Example 1 10 4.53 ≥3.0 qualified Example 2 10 4.38 ≥3.0 qualified Example 3 10 4.45 ≥3.0 qualified Example 4 10 4.22 ≥3.0 qualified Example 5 10 4.61 ≥3.0 qualified Comparative Example 1 10 3.65 ≥3.0 qualified Comparative Example 2 10 2.40 ≥3.0 Unqualified As shown in Table 2, the peel strength of Examples 1-5 is significantly higher than the standard requirement of ≥3.0 kgf / cm, with Example 5 reaching 4.61 kgf / cm and Example 1 reaching 4.53 kgf / cm. After 10 water washing cycles, the peel strength of each example decreased by no more than 12%, and there was no lifting or delamination at the edge of the reinforcing sheet, indicating that the reinforcing sheet of the present invention has excellent adhesion to the shoe upper and can withstand the high-frequency lateral shear forces during tennis.

[0050] Bending fatigue test After the reinforcing sheets of Examples 1-5 were attached to the inside of the shoe upper, they were repeatedly bent 20,000 times at a 90° bending angle and a frequency of 100 times per minute on a flexure tester. After the test, the edges of the reinforcing sheets and the attached surfaces were observed, and no cracks, delamination, or glue separation were found in any of the examples.

[0051] Actual wearing test The reinforcing plates from Example 1 and Comparative Example 2 were respectively attached to the inner side of the upper of a tennis shoe. The left foot wore the shoe with the reinforcing plate from Example 1, and the right foot wore the shoe with the reinforcing plate from Comparative Example 2. Two professional tennis players each played a total of 30 hours of high-intensity matches. After the test, the surface of the reinforcing plate from Example 1 on the left foot showed wear marks, but it did not wear through to expose the sole, and the reinforcing plate still completely covered the stress area on the inner side of the upper. On the right foot, the KPU reinforcing plate from Comparative Example 2 had worn through in the dragging area on the inner side of the upper, exposing the underlying upper fabric, and the fibers were broken.

[0052] Formula fine-tuning instructions During production, the proportions of butadiene rubber and EPDM rubber, the amount of aromatic oil, and the types and amounts of sulfur and vulcanization accelerators can be slightly adjusted within the range specified in this invention, depending on differences in workshop temperature, humidity, and the model of the internal mixer. The Mooney viscosity of the adjusted compound should be controlled at 50-70 ML(1+4)@100℃. The DIN wear of the reinforcing sheet is judged based on the test data not exceeding 50 mm3 across the entire temperature range from 30℃ to 100℃, with a typical control value of 34.2 mm3 at room temperature (30℃) and 37.8 mm3 at 100℃. The peel strength is judged based on a minimum of 3.0 kgf / cm under a sampling width of 10 mm ± 2, with a typical control value of 4.53 kgf / cm. All the above adjustments fall within the scope of protection claimed by this invention.

Claims

1. A heat-resistant friction-reinforcing sheet for tennis shoe uppers, characterized in that, It is made by molding vulcanization and freeze-setting of a compound rubber containing the following components in parts by weight: the freeze-setting involves transferring the sheet material, which is still at a temperature of 140-160°C after molding vulcanization, into a freezing environment of -10°C to -5°C within 30 seconds and treating it for 15-30 minutes. The compound comprises: Butadiene rubber: 60-70 parts; Polyisoprene rubber: 10-20 parts; EPDM rubber: 20-30 parts; Silica: 30-50 parts; Wear-resistant oil: 5-10 parts; Tetraneous zinc oxide whiskers: 3-8 parts; Sulfur: 1.5-2.5 parts; Vulcanization accelerator: 1-3 parts; 2-Methylbenzimidazole antioxidant: 1-3 parts; Stearic acid: 0.5-1.5 parts; PEG-4000: 1-3 parts; Protective wax: 0.5-1.5 parts.

2. The heat-resistant friction reinforcing sheet for tennis shoe uppers according to claim 1, characterized in that, The thickness of the reinforcing sheet is 1.0-2.5 mm.

3. The heat-resistant friction reinforcing sheet for tennis shoe uppers according to claim 1, characterized in that, The vulcanization accelerator is at least one of N-cyclohexyl-2-benzothiazole sulfenamide, dibenzothiazole disulfide, and tetramethylthiuram disulfide; the amount of sulfur used is 1.8-2.2 parts, and the amount of the vulcanization accelerator used is 1.5-2.5 parts.

4. The heat-resistant friction reinforcing sheet for tennis shoe uppers according to claim 1, characterized in that, The silica is precipitated silica.

5. The heat-resistant friction reinforcing sheet for tennis shoe uppers according to claim 1, characterized in that, The amount of the four needle-shaped zinc oxide whiskers is 4-6 parts.

6. The heat-resistant friction reinforcing sheet for tennis shoe uppers according to claim 1, characterized in that, The wear-resistant oil is an aromatic oil or a naphthenic oil.

7. A method for preparing a heat-resistant friction-reinforcing sheet for tennis shoe uppers as described in any one of claims 1 to 6, comprising the following steps: (1) Put the ingredients of the formula into an internal mixer and mix them evenly to make a compound; (2) Press the compounded rubber into a thin sheet with a thickness of 1.0-2.5 mm; (3) Place the thin film in a mold and mold it at a temperature of 140-160℃ and a pressure of 10-15MPa for 5-10 minutes to obtain a high-temperature sheet; (4) Transfer the high-temperature sheet to a freezing environment of -10°C to -5°C within 30 seconds and freeze-set for 15-30 minutes to obtain the reinforcing sheet.

8. The method for preparing the heat-resistant friction reinforcing sheet for tennis shoe uppers according to claim 7, characterized in that, It also includes step (5): grinding or corona treating the bonding surface of the reinforcing sheet, applying cold adhesive, and then bonding and fixing it to the inside of the tennis shoe upper by high-frequency current or hot pressing.

9. The method for preparing the heat-resistant friction reinforcing sheet for tennis shoe uppers according to claim 7, characterized in that, In step (1), butadiene rubber, polyisoprene rubber and ethylene propylene diene monomer rubber are first plasticized, and then 2-thiol-methylbenzimidazole antioxidant, stearic acid, PEG-4000 and protective wax are added. After mixing, silica, tetraneedle zinc oxide whiskers and wear-resistant oil are added, and then sulfur and vulcanization accelerator are added and mixed until uniform.

10. The method for preparing the heat-resistant friction reinforcing sheet for tennis shoe uppers according to claim 7 or 9, characterized in that, The compound obtained in step (1) has a Mooney viscosity ML(1+4)@100℃ of 50-70.